160k views
5 votes
I need the answer please. Because I think i got mine wrong

I need the answer please. Because I think i got mine wrong-example-1
User Dean Bates
by
5.6k points

2 Answers

3 votes

Answer:

a. 1 / 8^2 b. 3^3 c 1 / 6^4.

Explanation:

We used the following rules x^-n = 1/x^n,

1 / x^-n = x^n

and x^n * x^m = x^(n+m).

User Lee Boon Kong
by
5.4k points
1 vote

Answer:

see explanation

Explanation:

Using the rules of exponents


a^(-m)
(1)/(a^(m) )


a^(0) = 1


a^(m) ×
a^(n)
a^((m+n))

Given

(a)


8^(-2) =
(1)/(8^(2) )

(b)


(1)/(3^(-3) ) = 3³

(c)


6^(-12) ×
6^(8) ×
6^(0)

=
6^((-12+8)) × 1

=
6^(-4)

=
(1)/(6^(4) )

User Nicola Tuveri
by
6.2k points